Modifikasi Hammer Mill Sample Divider Untuk Penyederhanaan Fungsi Dengan Desain Ulang Pada PT. BV - Bernardus Valentcio Gonsalves; Burhan Nudin; Putri Endah Suwarni; Susanti Sundari (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
This study was conducted at PT. BV whose activities are in the coal mining sector, where there is a sample preparation process which aims to minimize the presence of impurities that will interfere with the coal analysis process. In the process there are two important tools used, namely the Hammer Mill and the Rotary Sample Divider. If we look at the use of these two separate tools, they are not efficient in terms of time, space and human resources, as a result the sample results are not optimal. So it is necessary to redesign the Hammer Mill machine and the Rotary Sample Divider machine by combining the two machines in one design, so that their function is simpler and more efficient, and also produces homogeneity in the coal samples to be analyzed. It is hoped that by combining the 2 tools used into one, we can overcome the lack of efficiency in sample preparation and get maximum results. The analysis used to identify problems uses a fishbone diagram to support identification, exploration, and depicts in detail all the causes related to this problem. The result of the redesign is a modified Hammer Mill Sample Divider that is more efficient and produces homogeneous coal samples to be analyzed. Apart from that, testing data on the sample preparation process using a modified Hammer Mill Sample Divider machine showed that the total testing time for 10 samples was obtained with an average time of 12.55 minutes, a maximum time limit of 14.02 minutes and a minimum time of 10.8 minutes and with the re-design of the Hammer Mill Sample Divider can minimize costs, use of human resources and time.. Keywords: Coal, Efficient, Hammer mill, Re-desain, Rotary sample divider, Sample preparation